Trivium vs. Trivium Toy - Castro Lechtaler, Antonio (2014)
We present the characteristic and minimal polynomials of the linear algorithms Trivium and Trivium Toy. We show the different cycles and mini-mum lengths obtained. The existence of initial states determining short cycles is verified. Finally, linear Trivium Toy is shown to be as cryptologically secure as the linear Trivium algorithm.